The role of stents in the treatment of congenital heart disease: Current status and future perspectives - Peters Bjoern; Ewert Peter; Berger Felix (Wolters Kluwer Medknow Publications, 2009)
Intravascular or intracardiac stenoses occur in many forms of congenital heart disease (CHD). Therefore, the implantation of stents has become an accepted interventional procedure for stenotic lesions in pediatric cardiology. Furthermore, stents are know to be used to exclude vessel aneurysm or to ensure patency of existing or newly created intracardiac communications. With the further refinement of the first generation of devices, a variety of "modern" stents with different design characteristics have evolved. Despite the tremendous technical improvement over the last 20 years, the "ideal stent" has not yet been developed. Therefore, the pediatric interventionalist has to decide which stent is suitable for each lesion. On this basis, currently available stents are discussed in regard to their advantages and disadvantages for common application in CHD. New concepts and designs developed to overcome some of the existing problems, like the failure of adaptation to somatic growth, are presented. Thus, in the future, biodegradable or growth stents might replace the currently used generation of stents. This might truly lead to widening indications for the use of stents in the treatment of CHD.